A dual-mode nanoparticle based on natural biomaterials for photoacoustic and magnetic resonance imaging of bone mesenchymal stem cells in vivo. Issue 60 (31st October 2019) - Zhang, Hua; Wang, Zhen-Jun; Wang, Ling-Jie; Li, Ting-Ting; He, Sheng; Li, Li-Ping; Li, Xiao-Yan; Liu, Shi-Jie; Li, Jian-Ding; Li, Si-Jin; Zhang, Rui-Ping
Abstract : Stem cell imaging in vivo is critical to elucidate the homing, distribution, survival, and repair mechanisms and to evaluate the therapeutic effects of engrafted stem cells. Abstract : Stem cell imaging in vivo is critical to elucidate the homing, distribution, survival, and repair mechanisms and to evaluate the therapeutic effects of engrafted stem cells. Unfortunately, unimodal imaging of stem cells does not simultaneously satisfy all current requirements owing to their intrinsic limitations. Obviously, bimodal or multimodal imaging of stem cells is a promising strategy for circumventing this issue. This study aimed to design and synthesize a novel dual-modal polyethylene glycol-modified magnetic nanoparticle (Fe 3+ -PEG-MNP) based on natural biomaterials including melanin and Fe ions for photoacoustic (PA) and magnetic resonance (MR) imaging of stem cells in vivo . The Fe 3+ -PEG-MNPs were characterized and their PA/MR imaging capability and cytotoxicity were evaluated. Bone marrow mesenchymal stem cells (BM-MSCs) labeled with Fe 3+ -PEG-MNPs were subjected to PA and MR imaging in vitro and in vivo . Consequently, Fe 3+ -PEG-MNPs displayed many superior properties, including ultra-small particle size, higher stability, water solubility, easy labeling of cells, lower cytotoxicity, high biosafety, excellent capability of PA/MR imaging, high sensitivity and long-term monitoring in vitro and in vivo . In particular, PA and MR signals of labeled BM-MSCs were maintained for at least 35 and 28 d, respectively, in vivo . Therefore, Fe 3+ -PEG-MNPs are ideal dual-modal PA/MR nanoparticles for non-invasive and effective monitoring of engrafted stem cells in vivo .